Increased heterogeneity of airway calibre in adult rats after hypoxia-induced intrauterine growth restriction - Wang, K.; Morton, J.; Davidge, S.; Larcombe, Alexander; James, A.; Donovan, G.; Noble, P. (Wiley-Blackwell Publishing Asia, 2017)
Background and objective: Intrauterine growth restriction (IUGR) is associated with asthma development. We hypothesized that IUGR disrupts airway development leading to postnatal structural abnormalities of the airway that predispose to disease. This study therefore examined structural changes to the airway and lung in a rat model of maternal hypoxia-induced IUGR. Methods: Pregnant rats were housed under hypoxic conditions (11.5% O2) from gestational days (GDs) 13 to 20 (pseudoglandular–canalicular stages, i.e. period of airway development) and then returned to normoxic conditions (21% O2). A control group of pregnant rats was housed under normoxic conditions throughout pregnancy. Weights of male offspring were recorded at birth and 7 weeks of age (adulthood), at which point lungs were fixed for morphometry and stereology (n = 6/group), or bronchoalveolar lavage fluid (BALF) was collected for cell counts (n = 6/group). Results: IUGR offspring were lighter at birth compared with control, but not at 7 weeks. While there was no difference in mean airway dimensions or lung volume, there was greater anatomical variation in airway lumen area in the IUGR group. A mathematical model of the human lung was used to show that greater heterogeneity in lumen area in IUGR-affected individuals increases bronchoconstriction during simulated bronchial challenge. More macrophages were identified in the BALF of IUGR offspring. Conclusion: The rat model demonstrates that IUGR leads to a more heterogeneous distribution of airway lumen calibre in adulthood with potential implications for bronchoconstriction in human subjects. Together with increased lung macrophages, these findings support a phenotypic shift after IUGR that may impact disease susceptibility.